Juries: acting out digital dilemmas to promote digital reflections - Vallejos, Elvira Perez; Pothong, Kruakae; Coleman, Stephen; Koene, Ansgar; Carter, Chris James; Statache, Ramona; Rodden, Tom; McAuley, Derek; Cano, Monica; Adolphs, Svenja; O'Malley, Claire (Association for Computing Machinery (ACM), 2015)
A quick journey through prevention science (e.g., substance misuse prevention) and a comparison between online and offline risks, harm, and vulnerability in children suggests that new approaches and interventions are needed to promote Internet safety and minimise the new sources of risk associated with accessing the Internet. In this paper we present a new methodological approach to promote digital literacy and positively influence the way in which young people interact with the Internet: iRights Youth Juries. These juries offer a solution for the challenge of how to engage children and young people in activities that, rather than simply promoting Internet safety, aim to provide the knowledge and the confidence required for developing healthy digital citizens. This approach thus begins to move beyond the notion of the Internet as a simple cause of social change, approaching it instead as an opportunity to engage knowledgeably with the digital world and maximise citizenship.